1988
DOI: 10.1177/088391158800300202
|View full text |Cite
|
Sign up to set email alerts
|

Novel Design of Microreservoir-Dispersed Matrices for Drug Delivery Formulations: Drug Release from Polybutadiene- and Poly (ethylene oxide)-Based Segmented Polyurethanes in Relation to Their Microdomain Structures

Abstract: Downloaded from 107 water structure in water swollen PEUU films. These results reveal that the ternary microdomain structures are composed of PBD, PEO, and hard segments.The drug release profiles of these PEUU devices are strongly affected by the physicochemical nature of soft segment matrices in PEUUs. The PEUUs with high PEO content exhibited slow and steady (zero-ordered) release of drug in contrast with those with low PEO content from which drug release was entirely restricted. This result indicates the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Although monolithic IVRs are expected to provide a non-linear diffusion profile governed by Fickian diffusion [53], the observed zero-order release profile is similar to that from nondegradable polyether urethanes shown previously by our group [15] and others [54][55][56]. Studies by Yui et al [55] have suggested that the formation of micro reservoirs of drugs in the microcrystalline hard domains, with the amorphous soft domains serving as transport channels, can lead to zero-order release profile. The release rate of 68 μg/day is comparable to that obtained in vitro from silicone rings (∼50 μg/day) which was obtained in clinical trials to create potentially inhibitory concentrations of Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Although monolithic IVRs are expected to provide a non-linear diffusion profile governed by Fickian diffusion [53], the observed zero-order release profile is similar to that from nondegradable polyether urethanes shown previously by our group [15] and others [54][55][56]. Studies by Yui et al [55] have suggested that the formation of micro reservoirs of drugs in the microcrystalline hard domains, with the amorphous soft domains serving as transport channels, can lead to zero-order release profile. The release rate of 68 μg/day is comparable to that obtained in vitro from silicone rings (∼50 μg/day) which was obtained in clinical trials to create potentially inhibitory concentrations of Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Tecoflex® 93A is a segmented polyurethane comprised of soft micro-domains of poly(tetramethylene oxide) and hard crystalline micro-domains of bis(4-isocyanatocyclohexyl)methane (H 12 MDI) and 1,4-butanediol. As a non-polar drug, Dex preferential interacts with the amorphous soft micro-domains of the polyurethane; these regions serve as drug reservoirs while empty hard crystalline micro-domains act as channels for drug release (35, 36). Similar results were reported by Gupta et.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the effect of differential partitioning of dapivirine in the hard crystalline and soft amorphous microdomains of the PU and/or due to the small partition coefficient of the drug between the PU and the sink conditions used. Studies conducted by Yui et al35, 46, 47 have theorized that the hard segments in a polyurethane matrix can act as reservoirs of drugs from where the drug is released through transport channels in the amorphous soft segment. The PU polymer consists of soft microdomains comprised of poly(tetramethylene oxide) which are connected by hard crystalline microdomains comprised of bis{4‐isocyanatocyclohexyl}methane (H 12 MDI) and 1,4‐butanediol.…”
Section: Discussionmentioning
confidence: 99%